Associations of egocentric social network characteristics with conversations about the harms of smoking and the benefits of quitting - Lizeth Cruz-Jiménez; James F. Thrasher; Victoria C. Lambert; Diego F. Leal; Rachel E. Davis; Chih-Hsiang Yang (PLoS ONE, 2026)
Background Although conversations initiated by smoking-cessation messages are associated with subsequent quit attempts, limited research has examined how the social network characteristics of people who smoke relate to engagement in these conversations. The current study aimed to assess associations between key social network attributes and conversations about the harms of smoking and the benefits of quitting in the context of exposure to novel cessation messages. Methods Data were collected from a convenience sample of U.S. adults who smoke (n = 366) and who received a 14-day supply of cigarettes in packs that four different labeling types (i.e., novel text-based messages about smoking harms on the side of packs; pictorial health warnings with the same text, but with imagery and printed on 50% of front and back of packs; efficacy-message inserts with text and imagery about smoking cessation benefits and quitting strategies, placed inside the packs; and/or efficacy message inserts with pictorial health warning labels). At baseline, participants reported their egocentric network characteristics, and each night for 14 consecutive days, they completed a survey about their conversations with network members in the prior 24 hours. Bivariate and adjusted mixed-effects logistic regression models, controlling for experimental message study condition and other covariates, assessed relationships between network attributes and conversations. We estimated separate models predicting the likelihood of conversations (1) about the harms of smoking and (2) about the benefits of quitting on any given day. Results In adjusted models, network members’ (i.e., alters’) disapproval of smoking and the prevalence of alters that smoke were positively associated with conversations about both smoking harms and quitting benefits. Network size was negatively associated with, and average closeness to alters was positively associated with, conversations about quitting benefits. Conclusion Social network characteristics can influence conversations about smoking harms and cessation benefits. Leveraging these features in cessation interventions could more effectively reduce smoking. Trial Registration: ClinicalTrials.gov NCT04075682